Dukungan Psikososial dalam Pelaksanaan Prevention of Mother to Child Transmission of HIV - Punjastuti, Budi (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Psychosocial support for mothers in the implementation of the Prevention ofMother to Child Transmission (PMTCT) of HIV is very important in reducing the psychosocialburden so that people living with HIV/AIDS (ODHA) continue to enjoy good quality of life andfunction well in society. PMTCT program in the Province of Yogyakarta has started from2006, and some existing hospitals such as Dr. Sardjito General Hospital routinely reported onthe program in 2006-2009. Dr. Sardjito General Hospital is a referral hospital for somehospitals in Yogyakarta to receive people with HIV / AIDS, especially pregnant women whichare HIV positive.Objective: To find out the overview of the mother's psychosocial support in theimplementation of the Prevention of Mother-to-Child Transmission (PMTCT) of HIV in Dr.Sardjito General Hospital, Yogyakarta.Methods: This was a qualitative study with a case study design. The research was conductedin Dr. Sardjito General Hospital, Yogyakarta. Data collection was done with in-depthinterviews on maternal psychosocial support in the implementation of the Prevention ofMother-to-Child Transmission (PMTCT) of HIV. Research subjects were 7 people and twoPMTCT officers taken by purposive sampling. Analysis of data was through some stagesnamely transcription, data reduction and coding, data presentation, conclusion drawing andverificationResults: The overview of support received by mothers in PMTCT implementation could beseen from the forms and sources of psychosocial support from family, relatives and healthpersonnel while from society it was not seen yet because the mothers had not been able toopen up about themselves. The impact of psychosocial support for mothers was that the lifebecame more meaningful and had more spirit, but in society the impact was not yet seenbecause the mothers were afraid to be isolated in the activity of the society environment.Conclusion: The mothers in the implementation of the Prevention of Mother-to-ChildTransmission (PMTCT) of HIV in Dr. Sardjito General Hospital, Yogyakarta, received fullsupport from the family but they had not been able to reveal their current condition to thepublic because of the fear that the public would not accept them leading to a feeling to beisolated and exiled. The officers had given their best services from the early time when themother knew to be infected by HIV and tried to eradicate stigma from other health providers.Keywords: Psychosocial Support, PMTCT of HIV